Exposure to the anti-microbial chemical triclosan disrupts keratinocyte function and skin integrity in a model of reconstructed human epidermis. Issue 1 (31st December 2023) - Baur, Rachel; Kashon, Michael; Lukomska, Ewa; Weatherly, Lisa M.; Shane, Hillary L.; Anderson, Stacey E.
Abstract: Triclosan is an anti-microbial chemical incorporated into products that are applied to the skin of healthcare workers. Exposure to triclosan has previously been shown to be associated with allergic disease in humans and impact the immune responses in animal models. Additionally, studies have shown that exposure to triclosan dermally activates the NLRP3 inflammasome and disrupts the skin barrier integrity in mice. The skin is the largest organ of the body and plays an important role as a physical barrier and regulator of the immune system. Alterations in the barrier and immune regulatory functions of the skin have been demonstrated to increase the risk of sensitization and development of allergic disease. In this study, the impact of triclosan exposure on the skin barrier and keratinocyte function was investigated using a model of reconstructed human epidermis. The apical surface of reconstructed human epidermis was exposed to triclosan (0.05–0.2%) once for 6, 24, or 48 h or daily for 5 consecutive days. Exposure to triclosan increased epidermal permeability and altered the expression of genes involved in formation of the skin barrier. Additionally, exposure to triclosan altered the expression patterns of several cytokines and growth factors. Together, these results suggest that exposure to triclosan impacts skin barrier integrity and function of human keratinocytes and suggests that these alterations may impact immune regulation.